Motivation in Learning English Focusing on Speaking Skills of Students at State Pariyatti Sasana University in Mandalay of Myanmar - Vasava; Kanokkamalade, Veerakarrn; Varamethi, Phramaha Suriya (วารสารพุทธจิตวิทยา, 2026)
This research investigated the motivation and satisfaction in learning English speaking skills among B.A. third-year students at State Pariyatti Sasana University in Mandalay, Myanmar. The study aimed to examine motivational levels and identify the factors influencing students' satisfaction with their language learning experience. Utilizing a mixed-method design, the researcher gathered data through questionnaires and in-depth interviews with a sample of 60 students and 5 English teachers. Quantitative data were analyzed using frequency, percentage, mean, and standard deviation, while qualitative data underwent content analysis. The findings revealed that students possessed a high level of motivation ( = 3.93, S.D. = 1.09) toward learning English speaking. The highest mean score was recorded for classroom-related speaking activities ( = 4.05), indicating that interactive and communicative environments significantly drive student engagement. While both integrative and instrumental motivations were high, instrumental motivation ( =3.96) was slightly more dominant. Students primarily viewed English proficiency as a vital tool for their future careers, academic advancement, and the global dissemination of Buddhist teachings. Additionally, the level of satisfaction with English instruction was high ( =3.63). Satisfaction was largely driven by supportive teacher feedback, peer interaction, and the use of culturally relevant materials. The study concludes that motivation and satisfaction form a reciprocal cycle that enhances speaking competence. Recommendations include adopting learner-centered activities and integrating Buddhist-related topics into the curriculum to sustain interest and foster communicative confidence among future Buddhist scholars.